SHUTTLE DIPLOMACY INDONESIA DI ASEAN TERKAIT KONFLIK LAUT TIONGKOK SELATAN - Muhammad Naufal Aziz (Andalas Institute of International Studies, 2019)
This research aim to analyze the succeeding factors of mediation inside the Shuttle Diplomacy that is conducted by Indonesia for two days in bringing together ASEAN countries voices after a deadlock on the 45th AMM meeting in Cambodia. Researchers refers to Lawrence Susskind and Eileen Babbitt works to explain why a mediation effort could work effectively, namely with the awareness of not carrying out unilateral actions, drafting alternative agreements to avoid ongoing conflict, delegates in negotiations are people who have authority and are committed in implement agreed actions, external factors that force the parties to seek a conflict resolution, the mediator is someone who could be accepted by all parties. This is a qualitative research with descriptive analysis methods to find the answers what makes shuttle diplomacy that is conducted by Indonesia could be working effectively. This research found that the mediation could be effective because there is awareness of each ASEAN country not to carry out unilateral actions towards the conflict, Marty Natalegawa proposed the Six Point Principle on the South China Sea draft as an alternative to communique that has failed before and ensured this agreement is obeyed by all parties, Indonesia’s role as mediator and the existence of other international interests also forcing ASEAN countries to determine a common perspective towards South China Sea conflict.